Sir Syed journal of education & social research SJESR. (Sir Syed College of Education, 2018)
Sir Syed Journal of Education & Social Research (SJESR) is a peer-reviewed, Open Access multi-disciplinary research journal that considers scholarly, research-based articles on all aspects of education and Social Sciences. SJESR encourage contributions from different educational systems and cultures around the world.